Notas sobre el epíteto a partir del valor epitético de los adjetivos compuestos de la épica arcaica griega - Plaza Picón, Francisca del Mar (Revista de Filología de la Universidad de La Laguna, 1991)
We deal with the epithetic value of homeric compound adjectives. In fact, from a linguistic point of view the epithetic value must be considered as belonging to performance (i.e. the saussurean parole), because it does only appear in the development of discours.